Silver-Mediated Perfluoroalkylation Reactions - Hafner, Andreas; Jung, Nicole; Bräse, Stefan (Synthesis, 2014)
Direct perfluoroalkylation reactions, especially trifluoromethylations of organic substrates, are of particular importance in modern organic chemistry as they allow rapid access to perfluoroalkylated molecules. In contrast to common metal-mediated perfluoroalkylations, recently developed silver-mediated perfluoroalkylation protocols offer the opportunity for orthogonal introduction of fluorine containing groups in organic compounds. This review gathers recent progress on silver-mediated perfluoroalkylation reactions and gives an overview over efficient syntheses, properties, and reactivity of perfluoroorganosilver(I) compounds. In addition, cooperative effects with copper-mediated processes are discussed.1 Introduction2 Syntheses and Properties of Perfluoroorganosilver Compounds3 Silver-Mediated Perfluoroalkylations 3.1 Perfluoroorganosilver Compounds in Copper-Mediated Perfluoroalkylations3.2 Perfluoroorganosilver Compounds as Precursors for Radicals3.3 Perfluoroorganosilver Compounds as Nucleophilic Reagents3.4 Silver-Catalyzed Perfluoroalkylations4 Conclusion and Outlook
Keywords: perfluoroalkylation; trifluoromethylation; silver; perfluoroorganyls; arenes